Deep ocean nutrients during the Last Glacial Maximum deduced from sponge silicon isotopic compositions - Hendry, K; Georg, R; Rickaby, R; Robinson, L; Halliday, A (2010)
The relative importance of biological and physical processes within the Southern Ocean for the storage of carbon and atmospheric pCO 2 on glacial-interglacial timescales remains uncertain. Understanding the impact of surface biological production on carbon export in the past relies on the reconstruction of the nutrient supply from upwelling deep waters. In particular, the upwelling of silicic acid (Si(OH) 4) is tightly coupled to carbon export in the Southern Ocean via diatom productivity. Here, we address how changes in deep water Si(OH) 4 concentrations can be reconstructed using the silicon isotopic composition of deep-sea sponges. We report δ 30Si of modern deep-sea sponge spicules and show that they reflect seawater Si(OH) 4 concentration. The fractionation factor of sponge δ 30Si compared to seawater δ 30Si shows a positive relationship with Si(OH) 4, which may be a growth rate effect. Application of this proxy in two down-core records from the Scotia Sea reveals that Si(OH) 4 concentrations in the deep Southern Ocean during the Last Glacial Maximum (LGM) were no different than today. Our result does not support a coupling of carbon and nutrient build up in an isolated deep ocean reservoir during the LGM. Our data, combined with records of stable isotopes from diatoms, are only consistent with enhanced LGM Southern Ocean nutrient utilization if there was also a concurrent reduction in diatom silicification or a shift from siliceous to organic-walled phytoplankton. © 2010 Elsevier B.V.